The effect of islamic corporate governance on internet financial reporting with risk disclosure as a moderator variable at Indonesian islamic banks - Angga Dwi Febrianto; Nur Khabib (Indonesian Journal of Islamic Economics Research, 2021)
This research is motivated by increasing the quality of internet use in various ways, one of which is as a business material in the world of Islamic banking. Islamic banking is required to report its operational activities following the times so that capital owners or customers are able to see banking performance more easily and efficiently. The purpose of this study is to find out the effect of islamic corporate governance on internet financial reporting with risk disclosure as a moderating variable case study at indonesian islamic commercial banks for the 2016-2020 period. The results show that the variables of the board of commissioners, institutional ownership and sharia supervisory board are able to influence internet financial reporting while the audit committee does not affect the internet. financial reporting. The variables of the board of commissioners, institutional ownership and sharia supervisory board moderated by risk disclosure are able to influence internet financial reporting while the audit committee moderated by risk disclosure does not affect internet financial reporting.